a) 9(x-2) = 63
9x - 18 = 63
9x = 63 + 18
9x = 81
x = 81 / 9
x = 9
c) 2(4x + 1) = 2(5x - 7)
8x + 2 = 10x - 14
8x - 10x = -14 - 2
-2x = -16
x = -16 / -2
x = 8
e) -4 - (6 - [-3 + (-3) + (-5 - x) - 7] - 9) = 1
-4 - (6 - [-3 - 3 - 5 + x - 7] - 9) = 1
-4 - (6 - [-8 + x - 7] - 9) = 1
-4 - (6 - [-15 + x]) - 9 = 1
-4 - (6 + 15 - x) - 9 = 1
-4 - 21 + x - 9 = 1
x - 34 = 1
x = 1 + 34
x = 35
b) 5(x + 3) = 2(5x - 5)
5x + 15 = 10x - 10
5x - 10x = -10 - 15
-5x = -25
x = -25 / -5
x = 5
d) 2(-x + 5) = -8(3x + 2) + 4
-2x + 10 = -24x - 16 + 4
-2x + 10 = -24x - 12
-2x + 24x = -12 - 10
22x = -22
x = -22 / 22
x = -1
f) -10 * {-2 - 2 * [(-4) * 5 / 44 - 2]} = -2x
-10 * {-2 - 2 * [-20 / 44 - 2]} = -2x
-10 * {-2 - 2 * [-0.4545 - 2]} = -2x
-10 * {-2 - 2 * [-2.4545]} = -2x
-10 * {-2 + 4.909} = -2x
-10 * {2.909} = -2x
-29.09 = -2x
x = -29.09 / -2
x = 14.545